12-months Clinical Evaluation of Fiber Reinforced Bulk Fill Resin Composite versus Incremental Packing of Nanohybrid Resin Composite in Restoration of Deep Proximal Lesions of Permanent Molars: A Randomized Controlled Trial - Mennatallah N. Salem; Olfat E. Hassanein; Dina W. ElKassas; Omar O. Shaalan (University of Zagreb. School of Dental Medicine, 2022)
Objective: The present clinical trial was conducted to evaluate the clinical performance of the biomimetic, bilayered structure utilizing a fiber reinforced bulk fill resin composite with a nanohybrid capping layer, compared to incremental packing of nanohybrid resin composite, in deep proximal cavities in permanent molars. Materials and methods: A total of 36 deep proximal cavities in vital molars were restored either with a bilayered structure of fiber reinforced composite resin as a dentine substitute and a capping layer of nanohybrid composite resin (n=18) or conventional, nanohybrid composite resin incrementation (n=18). The restorations were assessed over a period of 12 months using the modified USPHS criteria. The criteria evaluated were: fracture and retention, marginal integrity, marginal discoloration, anatomic form, proximal contact, surface texture, radiographic evaluation, postoperative sensitivity and secondary caries. Results: There was no statistically or clinically significant difference between fiber-reinforced resin composite and conventional incremental resin composite. There was no risk for failure regarding all the evaluated modified USPHS criteria for both materials after 12 months (RR= 1(95% CI 0.0209 to 47.8503; P =1.0000)). Conclusion: The biomimetic approach utilizing a fiber reinforced resin composite dentine substitute showed a comparable clinical performance to nanohybrid resin composite incrementation. Bulk fill fiber reinforced resin composite is an efficient alternative in restoration of deep proximal cavities in posterior teeth. Further long term studies are necessary to confirm these results.